Landing System Simulation Design to Improve Capacity at Soekarno-Hatta Airport - Rizki Rahmanda NIM 13413095 , Muhammad
Aircraft movement in Indonesia continues to increase each year, and this growth should be accommodated by all airports so that all the movement can be made. Accommodation should also be provided by Soekarno-Hatta Airport as the busiest airport in Indonesia. Based on the fact that the number of flight will increase in the future, it is necessary to increase the capacity at the airport to meet the demand. Planning to increase the capacity of the airport has been made by AirNav Indonesia, the runway operator in the airport, but still only in theory. Therefore, it is necessary to simulate the aircraft movement system at Soekarno-Hatta Airport, which includes its landing system, so that the value of the capacity can be seen clearly for each scenario. This study uses data related to the entire landing system at the airport, including the wind direction, the inter arrival time, destination, type, and speed of the aircraft as input data. Collected data is then entered to provide the detail in a simulation model created using Arena Simulation software. Results of the simulation are then combined with the aircraft departure simulation model so the Airport simulation as a whole can be created and can be used to assess the performance of the system. The performance criteria of the measured system are the number of takeoff and arrival processes that can occur in a single time and also the average queue time on the airport taxiway. Results of the current system are then compared with the proposed capacity improvement plan, such as using a different operation mode for the runway and the addition of road in the taxiway by looking at the queue of the existing system. From the comparison and analysis from the results, it can be seen that the airport capacity still can be improved by applying the solution design.